Islamic Education With Technology (ICT) Insight - Robbiy Maula Betaraya (AIUA Journal of Islamic Education, 2020)
This paper is motivated by the rapid development of technology. One of the aspects affected by the development of technology is in the field of education. Technological advances have a significant impact on the implementation of education. Technology facilitates and assists educational activities, both for educators, education staff, education providers and also for students. Technology can be used as an appropriate learning media for teaching and learning activities because it facilitates the delivery of material to students. This study aims to explain Islamic religious education with a technology perspective. This research is library research. Namely making library materials as the main source (data), so that it is more of a document research (documentary research). Thus, in this literature research the author wants to analyze thoughts about Islamic religious education that are technologically oriented. The method of collecting data in this research is by collecting literature related to Islamic religious education and technological developments to be used as primary materials. The results of this study are (1) educational technology, an application of technology that supports all forms of learning process activities in the form of infrastructure, systems, or methods to obtain, store, process and convey information that can be accounted for which aims as a tool to improve and improve the learning process of students (2) The use of information and communication technology can expand the scope of the paradigm and curriculum of Islamic Religious Education and integrate Islamic Religious Education with modern education (3) The role of ICT in learning basically functions as a learning medium to be used as a tool demonstration (4) examples of technology-oriented PAI are visual-based, audio-based, audio-visual, and Internet-based.